计算:(1/根号(2)+1+1/根号(3)+根号(2)+1/2+根号(3)+...+1/根号(2015)+根号(2014)(根号(2015)+1)=________

来源:学生作业帮助网 编辑:作业帮 时间:2017/12/16 17:19:22
计算:(1/根号(2)+1+1/根号(3)+根号(2)+1/2+根号(3)+...+1/根号(2015)+根号(2014)(根号(2015)+1)=________计算:(1/根号(2)+1+1/根号

计算:(1/根号(2)+1+1/根号(3)+根号(2)+1/2+根号(3)+...+1/根号(2015)+根号(2014)(根号(2015)+1)=________
计算:(1/根号(2)+1+1/根号(3)+根号(2)+1/2+根号(3)+...+1/根号(2015)+根号(2014)(根号(2015)+1)=________

计算:(1/根号(2)+1+1/根号(3)+根号(2)+1/2+根号(3)+...+1/根号(2015)+根号(2014)(根号(2015)+1)=________
【1/(√2+1)+1/(√3+√2)+1/(2+√3)+...+1/(√2015+√2014)】(√2015+1)
=(√2-1+√3-√2+√4-√3+……+√2015-√2014)(√2015+1)————分母有理化
=(√2015-1)(√2015+1)
=2015-1
=2014